Exploitation of the fibrinolytic system by B-cell acute lymphoblastic leukemia and its therapeutic targeting - Valentina R. Minciacchi; Jimena Bravo; Christina Karantanou; Raquel S. Pereira; Costanza Zanetti; Rahul Kumar; Nathalie Thomasberger; Pablo Llavona; Theresa Krack; Katrin Bankov; Melanie Meister; Sylvia Hartmann; et al. (Nature Communications)
Abstract Fibrinolysis influences the mobilization of hematopoietic stem cells from their bone marrow microenvironment (BMM). Here we show that activation of plasmin, a key fibrinolytic agent, by annexin A2 (ANXA2) distinctly impacts progression of BCR-ABL1+ B-cell acute lymphoblastic leukemia (B-ALL) via modulation of the extracellular matrix (ECM) in the BMM. The dense ECM in a BMM with decreased plasmin activity entraps insulin-like growth factor (IGF) 1 and reduces mTORC2-dependent signaling and proliferation of B-ALL cells. Conversely, B-ALL conditions the BMM to induce hepatic generation of plasminogen, the plasmin precursor. Treatment with ε-aminocaproic acid (EACA), which inhibits plasmin activation, reduces tumor burden and prolongs survival, including in xenogeneic models via increased fibronectin in the BMM. Human data confirm that IGF1 and fibronectin staining in trephine biopsies are correlated. Our studies suggest that fibrinolysis-mediated ECM remodeling and subsequent growth factor release influence B-ALL progression and inhibition of this process by EACA may be beneficial as adjunct therapy.